En pos del Dios Supremo en la antigua China - Damboriena, Prudencio (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 1948)
China has never stopped recognizing the Sovereign of Heaven or honoring him with sacrifices of oblation and supplication. To meditate on this heritage, we look back to the origins of the Chinese people and, based on the objectivity of history and its auxiliary sciences, we try to find that belief in a Supreme Lord, which is the best preparation that the people can show for the acceptance of Christianity.